Social Media as a Counter Space for the Motherhood Community in Creating Counter-Hegemony - Indranila, Ardhani (JURNAL KOMUNIKASI INDONESIA, 2022)
This article explores how the emergence of the online community of motherhood on social media can become a medium of counter-hegemony against the discourse of motherhood. The concept of “ibuism” as a picture of an ideal mother’s parenting form in Indonesia is justified as the standard of a “good mother” that has been socially constructed for a long time. The dominant discourse has been internalized from generation to generation by Indonesian women. However, this discourse negates other narratives that are important for women. Therefore, the online motherhood community on social media emerged to overcome these challenges and mobilize women to provide opposing narratives through social media as counter space. By using the perspectives of Counterpublic and Counter-Hegemony, the researcher argues that online communities on social media have the power to construct new discourses against hegemony. Specifically, the researcher argues that social media is an alternative space to fight dominant narratives, especially those taboo to discuss. This qualitative study will look at the Halo Ibu community and the Komunitas Ibu Profesional (Professional Mother Community) on Instagram through content observations and interviews. In conclusion, the emergence of online communities on social media can act as an agency to create counter-narratives through content and the use of social media as a space of resistance.